Dynamic Adjustment: The Transformation of Trilateral Relations between China, the United States and Latin America (1949-2023) - Jiang, Meijie (Ibero-América Studies, 2024)
This paper examines the transformative dynamics of the trilateral relationship between the United States, China, and Latin America from the 1950s to the present. Through the lens of national role theory, it explores how the national roles of these actors have shifted in response to geopolitical, economic, and ideological changes. The study is structured chronologically, analyzing distinct periods that mark the evolution of this trilateral dynamic. It delves into the historical evolution of roles and interactions, policy shifts, and strategic calculations to offer insights into the complexities of trilateral relations. The paper contributes to the literature by highlighting the interplay between self-perceived national roles and external expectations, and it provides a nuanced perspective on the challenges and opportunities inherent in navigating the multifaceted interactions between the US, China, and Latin America. The research aims to enhance understanding of the broader geopolitical trends and regional dynamics that have influenced the trajectory of these relations, offering implications for global politics, regional stability, and economic development.